Effect of polymerization mode of two adhesive systems on push-out bond strength of fiber post to different regions of root canal dentin - Shahram Farzin Ebrahimi; Niloofar Shadman; Ehsan Baradaran Nasery; Farid Sadeghian (Wolters Kluwer Medknow Publications, 2014)
Background: A few studies have investigated the effect of the activation mode of adhesive systems on bond strength of fiber posts to root canal dentin. This study investigated the push-out bond strengths of a glass fiber post to different root canal regions with the use of two adhesives with light- and dual-cure polymerization modes. Materials and Methods: In this in vitro study, 40 maxillary central incisors were decoronated at cement-enamel junction with 15 ± 1 mm root length. After root canal therapy and post space preparations, they were randomly divided into four groups. Post spaces were treated with four different adhesives: Excite, Excite Dual cure Single Component (DSC), self-etch adhesive (AdheSE), and AdheSE dual-cure. Then the fiber-reinforced composite (FRC) post, Postec Plus, was cemented with dual-cure resin cement, Variolink II. The roots were cut into three 2-mm-thick slices. Push-out tests were performed with a universal testing machine at a crosshead speed of 0.5 mm/min. The mode of failures was determined under a stereomicroscope. Data were analyzed by three-way analysis of variance (ANOVA) and Tukey test was conducted to compare post hoc with P < 0.05 as the level of significance. Results: The highest bond strength was obtained for AdheSE dual-cure (15.54 ± 6.90 MPa) and the lowest was obtained for Excite light-cure (10.07 ± 7.45 MPa) and only the bond strength between these two adhesives had significant difference (P = 0.02). Bond strength decreased from the coronal to the apical in all groups and this was significant in Excite (group 1) and AdheSE (group 3) (P < 0.001). In apical regions, bond strength of dual-cure adhesives was significantly higher than light-cure adhesives (P < 0.001). Conclusion: Push-out bond strength of fiber post to different regions of root canal dentin was affected by both adhesive systems and their polymerization modes.